Karakteristik Wisatawan Pada Program City Tour Kota Denpasar - Putra, Anak Agung Surya Brahmana; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
Denpasar Heritage City Tour is a recreation program based in Denpasar. This program was set to adjust the number of tourists to the city of Denpasar in particular. In the implementation of this program is still not very well known and used by tourists, but this program has run better. This study aims to find out how the tourism city of Denpasar and the characteristics of users of city tour program. Collection data of this study techniques are observation, in-depth interviews, documentation studies and questionnaires. The thechnique of data analysist was used in this research by qualitative data analysis. This data indicate that it focus to the tourism in the city of Denpasar at this time and the questionnaire’s result was choosen and calculated to determine the characteristics of tourists using the City Tour package. This study’s result has indicated that the tourists characteristic of program city tour by sex, tourists City Tour dominated by women, according to the age of tourists on the City Tour package users dominated 31-40 years old, according to the origin of the user City Tour package users in the dominance of the Asian continent, according to the tourist status of the City Tour user is dominated by married couples, depends on the level of education of the last tourists City Tour users dominated by scholars, according to monthly income Tourist Tour Tour dominated tourist income an average of 4 million and above and according to work User City Tour is dominated by private employees. Keywords : Tourism Denpasar, City Tour Program